Study of Telemental Health Services for Veterans from Viewpoints of Experts - Maryam Ahmadi; Tayebeh Noori; Kambiz Bahaadin Beigy; Esmaeil Mehraeen (Tehran University of Medical Sciences, 2016)
Background and Aim: For more than forty years, telemental health services have been used as a successful mean in various fields such as treatment and preventive interventions. This study was aimed to determine the viewpoints of health information management (HIM), and mental health professionals about telemental health services for veterans with mental disorders. Materials and Methods: This cross-sectional survey was conducted in 2013. The study population consisted of two groups: the first group included mental health professionals working in psychiatric hospitals in Tehran and the second group comprised HIM professionals. The data were collected using a questionnaire that its validity was confirmed by experts and the reliability was estimated through test-retest method. The data analysis was performed using SPSS 17.0 and descriptive statistics. Results: The findings showed that from the mental health expertschr('39') viewpoints, highest impact of the use of telemental health services related to medical travel costs with average 4.37 and the lowest impact replacement with the face to face treatment with average 2.68. Conclusion: In general, the groups participating in this study stated that in situations where access to care was difficult, telemental health services could be used as a reliable alternative for the war disabled care needs. Therefore, it is suggested that Iranian foundation of Martyrs and Veterans Affairs and the health system administrators take more serious measures for the implementation of telemedicine for veterans.